Price Discovery in Informationally-Linked Markets: A Microstructure Analysis of Nikkei 225 Futures - Covrig, V. (Institutional Knowledge at Singapore Management University, 2004)
As the process of globalization of trading and competition among exchanges for order flow accelerates, it is important to determine the information revelation and price discovery in informationally-linked markets. This paper examines the intradaily price discovery process of Nikkei 225 index in three competing markets -- the domestic spot market (Tokyo Stock Exchange), the domestic futures market (Osaka Securities Exchange), and the foreign futures market (Singapore Exchange). The evidence suggests that the futures market contributes more than 75% to price discovery, with the Osaka Securities Exchange contributing more than 57% of the futures markets and 43% of total information share. Surprisingly, the Singapore Exchange has a contribution of 43% of the futures and 33% of the total price discovery, which far exceed its share of trading volume. This suggests that a small “satellite” market can co-exist with a large “home” market and play a significant role in the price discovery process by being a niche player.